Hubungan Usia Menarche dengan Kejadian Kanker Ovarium - Marina Tandarto; Erwin Ginting; M. Khairul Nuryanto (Husada Mahakam, 2020)
Ovarian cancer is the 7th most common cancer and the 8th most common cause of death in women worldwide. In the year 2012, Indonesia constitute as a country with the 3rd largest amount of cases of ovarian cancer in Asia; with mortality rate of 7,075 out of a total of 10,238 patients nationwide. There are several factors that are thought to influence the risk of ovarian cancer, one of them is the age of menarche. This study aims to determine the effect of menarche age on the incidence of ovarian cancer in Abdul Wahab Sjahranie Hospital Samarinda. This research is an observational analytic study with cross sectional design using purposive sampling technique. The research instrument was carried out using medical records. The results obtained as many as 82 respondents who met the inclusion and exclusion criteria where there were 20 patients diagnosed with ovarian cancer and 62 patients who were not diagnosed with ovarian cancer. The data was analysed using the Somer's d test. The results showed that there was no influence of age of menarche on the incidence of ovarian cancer with the value of p = 0.323 (p> 0.05). Keywords : Age of Menarche, Ovarian Cancer